Upaya Guru Dalam Manajemen Pembelajaran Berbasis Kelompok Pada Anak Usia Dini Di Tk Aisyah Kab. Bengkulu Tengah - Sirna Yenti; Mimpira Haryono; Ela Pebriani (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to determine the efforts of teachers in group-based learning management for early childhood at Aisyah Kindergarten, Central Bengkulu Regency, which includes planning, organizing, implementing, and evaluating learning. This study uses a qualitative research method with a descriptive approach. The research subjects consisted of the principal and teachers. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that group-based learning management at Aisyah Kindergarten, Central Bengkulu Regency has been implemented well. Teachers prepare learning materials, organize study groups, carry out active play-while-learning activities, and conduct evaluations through observation and documentation of children's development. Group-based learning helps children be more active, able to work together, communicate, and interact with their peers. Based on the results of the study, it can be concluded that group-based learning management has a positive influence on social development and children's involvement in the learning process, thereby creating an active, orderly, and enjoyable learning atmosphere for early childhood.